LEADERSHIP STYLE AND NATIONAL SECURITY IN NIGERIA: AN ASSESSMENT OF EBELE GOOD LUCK JONATHAN AND MUHAMMADU BUHARI’S ADMINISTRATIONS - OLAYINKA BABATUNDE ADEBOGUN; JOSEPH OLATUNJI ODUNTAN; ABRAHAM EDEH (International Studies Journal)
This study investigates the assessment of political leadership and implications for national security in Nigeria’s fourth republicwith a specific focus on Former President Good-Luck Jonathan and President Muhamaddu Buhari’s Administration. The objectives of the study examinedthe effect ofpolitical leadership on national security. The study employed secondary data in gathering information from books, newspapers, Journals, magazines, and internet sources. Transformational Leadership theory was adopted in this study. It was found in the study that the state of insecurity which manifested inits variousforms such as terrorism, militancy, kidnapping, corruption, poverty, unemployment, violation of human rights, and underdevelopment of some regions in the country is a result of political leadershipby various Nigerian leaders in their respective administration and this has seriouseffects on the security of the country. The study proposesthat politicalleaders ofthe Nigerian state should protect the interest of their people rather than their own personal interests.